The snow hare - Lichtarowicz, Paula (Little, Brown and Company, 2023)
"Lena has lived a long, quiet life on her farm in Wales, alongside her husband and child. But as her end approaches, buried memories begin to return. Of her childhood in Poland, and her passion for science. Of the early days of her marriage, reluctant wife to an army officer. Of the birth of her daughter, whose arrival changed everything. Memories less welcome return, too. Her Polish village, transformed overnight by the Soviets, and the war that doomed her entire family to the frigid work camps of the Siberian tundra. And buried in that blinding snow, amongst the darkness of survival, the most haunting memory of all: that of an extraordinary new love"--